2021
DOI: 10.1155/2021/9949697
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Aggravates Calcium Oxalate Stone Formation via PPK1/Flagellin‐Mediated Renal Oxidative Injury and Inflammation

Abstract: Escherichia coli (E. coli) is closely associated with the formation of kidney stones. However, the role of E. coli in CaOx stone formation is not well understood. We explored whether E. coli facilitate CaOx stone formation and its mechanism. Stone and urine cultures were reviewed from kidney stone formers. The ability of calcium oxalate monohydrate (COM) aggregation was detected to evaluate the influence of uropathogenic E. coli, then gel electrophoresis and nanoLC-MS/MS to detect the crystal-adhered protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…2019; An et al . 2021), and E. coli is one of the most commonly identified organisms in stone cultures (Parkhomenko et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
“…2019; An et al . 2021), and E. coli is one of the most commonly identified organisms in stone cultures (Parkhomenko et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have reported that damaged cells develop lesions that induce the retention of particles on the surface of renal papillae, and crystals become attached to damaged renal tubular cells [ 30 , 31 ]. In addition, both UCC and HBV infection may share a common pathogenesis or exacerbating factors as Porter et al [ 32 ] reported and immunosuppression could promote both HBV infection and urinary tract infections, while pathogens such as E. coli in urine could promote the formation of stones [ 33 ]. HBV infection of renal tubular epithelial cells may increase the risk of UUC formation by causing changes in renal tubular acid function or promoting the accumulation and growth of calcium crystals.…”
Section: Discussionmentioning
confidence: 99%
“…The body weights were recorded on the first and third days. The transurethral injection of E. coli to induce the UTI model was performed as previously described ( An et al, 2021 ). The 12 rats were randomly divided into two groups as follows: group 1 was the normal control group, while group 2 received E. coli .…”
Section: Methodsmentioning
confidence: 99%